2022
DOI: 10.1371/journal.pone.0262945
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparities in cardiac transplantation: Chronological perspective and outcomes

Abstract: Background The objective of this study was to evaluate annual heart transplant volumes and 3-year post-transplant outcomes since establishment of United Network for Organ Sharing (UNOS) database stratified by race. Methods The UNOS thoracic transplant database was evaluated for adult patients since 1987. The available database was then stratified by Race: Black, White and Other and era of transplant: group 1(1987–1991), group 2(1992–1996), group 3(1997–2001), group 4(2002–2006), group 5(2007–2011), group 6(2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…Compared to White patients, Black and Native American patients were less likely to receive liver transplants while Asians and Hispanic patients were more likely to. Multiple studies have shown similar racial disparities in other organ transplantation fields such as bone marrow, renal, and heart transplantation [19][20][21][22][23][24][25]. Interestingly, Moylan et al previously demonstrated that race was not significantly associated with liver transplantation or death in the post-MELD era; however, they found that non-White patients were often listed at a more advanced stage of disease [14].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to White patients, Black and Native American patients were less likely to receive liver transplants while Asians and Hispanic patients were more likely to. Multiple studies have shown similar racial disparities in other organ transplantation fields such as bone marrow, renal, and heart transplantation [19][20][21][22][23][24][25]. Interestingly, Moylan et al previously demonstrated that race was not significantly associated with liver transplantation or death in the post-MELD era; however, they found that non-White patients were often listed at a more advanced stage of disease [14].…”
Section: Discussionmentioning
confidence: 99%
“…Several single-center studies have suggested that advances in transplant recipient selection, care of patients awaiting a heart transplant, and post-transplant care of transplant recipients have contributed to early survival improvements following transplantation for both white and Black patients [ 22 24 ]. A recent study using the UNOS database found that the historically poor survival of adult Black heart transplant recipients has gradually improved and became comparable to that of white transplant recipients [ 25 ]. General improvement in care, better compliance with the immunosuppression, reliable insurance coverage and increased awareness about reducing racial disparities in recent years could be contributing factors in improved survival of Black patients [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Black heart transplant recipients are historically reported to be at high risk of graft failure and all-cause mortality, 1,2,17 although a recent study by Trivedi et al reported improved post-transplant survival at 3-years in the most recent era. 18 They suggested that this improvement may be due to multiple factors including improved care, better compliance with immunosuppression, reliable insurance, and increased awareness about reducing racial disparities. Socioeconomic factors such as low levels of education and less insurance coverage have been highlighted as contributing to the worse outcomes in Black patients, but other biological factors have also been implicated.…”
Section: Discussionmentioning
confidence: 99%
“…Black heart transplant recipients are historically reported to be at high risk of graft failure and all‐cause mortality, 1,2,17 although a recent study by Trivedi et al reported improved post‐transplant survival at 3‐years in the most recent era 18 . They suggested that this improvement may be due to multiple factors including improved care, better compliance with immunosuppression, reliable insurance, and increased awareness about reducing racial disparities.…”
Section: Discussionmentioning
confidence: 99%